Infrared: A Key Technology for Security Systems. (4th December 2012) - Corsi, Carlo
Abstract : Infrared science and technology has been, since the first applications, mainly dedicated to security and surveillance especially in military field, besides specialized techniques in thermal imaging for medical diagnostic and building structures and recently in energy savings and aerospace context. Till recently the security applications were mainly based on thermal imaging as surveillance and warning military systems. In all these applications the advent of room temperature, more reliable due to the coolers avoidance, low cost, and, overall, completely integrable with Silicon technology FPAs, especially designed and tailored for specific applications, smart sensors, has really been impacted with revolutionary and new ideas and system concepts in all the infrared fields, especially for security applications. Lastly, the advent of reliable Infrared Solid State Laser Sources, operating up to the Long Infrared Wavelength Band and the new emerging techniques in Far Infrared Submillimeter Terahertz Bands, has opened wide and new areas for developing new, advanced security systems. A review of all the items with evidence of the weak and the strong points of each item, especially considering possible future developments, will be reported and discussed.